2015
DOI: 10.1007/s00520-015-3037-6
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination of chemotherapy patients—effect of guideline implementation

Abstract: 156 wordsManuscript 1415 words 2 Abstract Purpose: Despite substantial morbidity and mortality of influenza and pneumococcal infections in cancer patients treated with chemotherapy, vaccination against both illnesses is infrequent. We evaluated the impact of implementation of clinical guidelines on vaccination of chemotherapy patients treated in our institute. Methods:Prospective audit before (2012) and after (2013)(2014)) the introduction of immunisation guidelines for chemotherapy patients in a UK tertiary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 14 publications
0
12
1
1
Order By: Relevance
“…A guideline implementation study was associated with a significant increase in the rate of pneumococcal vaccination (47 vs. 25%, P= 0.0018) in a tertiary cancer center. 18 A continuous medical education program using live meetings, patient handouts, posters web based applications and organized by an interdisciplinary steering committee significantly improved immunization rates of patients and medical staff.…”
Section: Discussionmentioning
confidence: 99%
“…A guideline implementation study was associated with a significant increase in the rate of pneumococcal vaccination (47 vs. 25%, P= 0.0018) in a tertiary cancer center. 18 A continuous medical education program using live meetings, patient handouts, posters web based applications and organized by an interdisciplinary steering committee significantly improved immunization rates of patients and medical staff.…”
Section: Discussionmentioning
confidence: 99%
“…In those not vaccinated prior to receiving cytotoxic therapy, some experts recommend delaying vaccination up to 6 months after chemotherapy is completed to ensure greater efficacy. The effectiveness of the current recommendations in reducing disease burden remains unclear, potentially due to underutilization of vaccines in the cancer population resulting from confusion about the utility of vaccination in patients who are receiving myeloablative treatments, even in tertiary cancer centers [93]. …”
Section: Introductionmentioning
confidence: 99%
“…A recent Cochrane review suggested that there are more benefits than risks for influenza vaccination among cancer patients [19]. Likewise, the use of pneumococcal vaccination to decrease the chances of pneumonia among cancer patients has been recommended by many international bodies [20]. However, adherence to both forms of vaccination was found to be low and more work is needed to improve compliance [21][22][23].…”
Section: Discussionmentioning
confidence: 99%